COVID-19-related anxiety and knowledge toward its preventive measures among patients with chronic medical illness on follow-up in public hospitals of Bale, East Bale, and West Arsi zones, Ethiopia. (January 2022) - Yasin, Ahmed; Asefa, Tesfaye; Takele, Abule; Fikadu, Genet; Sahiledengle, Biniyam; Tura, Birhanu; Gemmechu, Addisu; Abduku, Mohammed awel; Zenbaba, Demisu; Tesa, Edao; Tasew, Alelign; Tekalign, Yohannes; et al.
Background: Coronavirus disease 2019, also known as 2019-nCoV cluster of acute respiratory illness with unknown causes, which occurred in Wuhan, Hubei Province, in China, was first reported to World Health Organization country office as of December 30, 2019. People with medical illness are at a higher risk for coronavirus disease, and the pandemic influences mental health and causes psychological problems, particularly in those with chronic medical illness. Hence, this study aimed to assess coronavirus disease 2019-related anxiety and the knowledge on its preventive measures among patients with medical illness on follow-up in public hospitals of Bale, East Bale, and Arsi zones Objective: To assess coronavirus disease 2019-related anxiety and knowledge toward coronavirus disease 2019 preventive measures among patients with chronic medical illness on follow-up in public hospitals of Bale, East Bale, and West Arsi zones. Methods: A hospital-based cross-sectional study was conducted in selected hospitals of Bale and West Arsi zones, Southeast Ethiopia. A total of 633 study participants were included in this study, and data were collected through an interviewer-administered questionnaire. A descriptive summary was computed. Bivariable and multivariable logistic regression analyses were carried out to identify the associated factors. Results: Overall, the prevalence of anxiety among chronic patients in this study was 6.3% (95% confidence interval: 4.6%–8.5%) and 420 (66.35%) had good knowledge on the preventive measures of coronavirus disease 2019. Factors significantly associated with anxiety among chronic patients were being educated (95% confidence interval: adjusted odds ratio = 0.26 (0.09–0.74)), being male (95% confidence interval: 2.69 (1.11–6.53)), and use of mask (95% confidence interval: 0.11 (0.05–0.26)). Conclusion: The prevalence of coronavirus disease 2019-related anxiety among chronic patients was high and being males, uneducated, and not using face mask was significantly associated with coronavirus disease 2019-related anxiety.